State Estimation for Switched Time-Varying Systems with Delay and Nonlinear Disturbance: An Integral Inequality Method - Fanwei Meng; Yuangong Sun (Discrete Dynamics in Nature and Society)
This paper focuses on the problem of state estimation for certain switched time-varying systems with time-varying delay and nonlinear disturbance. By using an integral inequality technique and a method used in positive systems, we have established several explicit criteria for state estimation of the system, which reduce to stability criteria for some particular cases. The involved nonlinear disturbance of the system takes more general form including both the internal disturbance and the external disturbance. Three numerical examples are also given to verify the validity of the obtained theoretical results.